TEACHING WRITING DESCRIPTIVE TEXT BY USING FACEBOOK AT SEVENTH GRADE SMPN 1 SEMEN - Wahyuni, Qilya Esti; Rohmad, Ali (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
The purpose of this research is to find out whether Facebook is effective or not in teaching writing descriptive text. This research employed a quantitative approach of using true experimental. Meanwhile, the research using Post-test Only Control Design for writing skill. The research was conducted in the seventh grade of SMPN 1 Semen in academic year 2018/2019. This research using 2 class as the sample, experimental group and control group. To get the result of the research, this research using test. The mean score of experimental group is 72.50 in a good category. Meanwhile, the mean score of control group is 57.83 in fair category. The result of independent sample test show that there is significant difference between experimental group which is taught by using Facebook and control group which is not taught by using Facebook. The alternative hypothesis stated that Facebook is effective to be used in writing descriptive text at the seventh grade of SMPN 1 Semen.